Spatial variations and pools of non-structural carbohydrates in young Catalpa bungei undergoing different fertilization regimes - Guan, Zhuizhui; Lu, Qifeng; Lin, Yubiao; Lin, Daiyi; Lu, Yizeng; Han, Qingjun; Li, Ningning; Ma, Wenjun; Wang, Junhui; Su, Yan; Li, Jiyue; Qiu, Quan; et al. (Frontiers in Plant Science, 2022)
Despite the importance of non-structural carbohydrates (NSC) for growth and survival in woody plants, we know little about whole-tree NSC storage. Here, Catalpa bungei trees fertilized using different schedules, including water and fertilizer integration, hole application, and no fertilization, were used to measure the spatial changes of NSC concentrations in the leaf, branch, stem, bark, and root. By calculating the volume of whole-tree NSC pools and the contribution of distinct organs, we were also able to compare the storage under various fertilization regimes. We discovered that each organ undergoing various fertilization mechanisms had patterns of spatial distribution that were quite comparable. Height-related increases in the sugar and NSC concentrations of the leaf and bark were observed. The concentrations of sugar, starch, and NSC in the branch did not appear to vary longitudinally or horizontally. With height, the sugar and NSC concentrations of the stem first dropped and then rose. In comparison to fine root, the coarse root contained larger amounts of NSC components. Contrary to no fertilization, fertilization enhanced the distribution ratio of the leaf, branch, and stem NSC pools while decreasing the distribution ratio of the root NSC pool. In particular, the addition of fertilizer and water dramatically boosted the biomass of the organs, improving the carbon sink of each organ and the tree as a whole. Our main goal was to strengthen the empirical groundwork for comprehending the functional significance of NSC allocation and stock variations at the organ-level of C. bungei trees.